(untitled) (Research, Society and Development, 2022)
Introduction: Episiotomy (EP) is a surgical intervention performed on the perineum and posterior wall of the vagina during childbirth to increase the passageway of the fetus and prevent injury. However, their accomplishments bring complications to the pelvic floor musculature (PFM) and the woman’s quality of life. Thus, physiotherapy seeks to prepare the PFM during pregnancy so that it is strong and flexible for childbirth. Objective: This study aims to carry out an integrative review in order to gather evidence from the literature about the contribution of physiotherapy to preventing the need to perform an episiotomy technique during labor. Methodology: This is an integrative literature review on the Scielo and PubMED platforms. Results: 67 studies were found and, after inclusion and exclusion criteria, a total of 5 articles were selected for the composition of the study. Discussion: Among the physiotherapeutic resources to prevent episiotomy, perineal massage and PFM contraction exercises stand out. Conclusion: Thus, it is concluded that physiotherapy develops strong results for the prevention of perineal injuries and their complications.